Teaching Narrative Reading by Using the Sub-text Strategy for Islamic Senior High School Students - Muhamad Holandyah; Nova Lingga Pitaloka; Wahyudiyanto Wahyudiyanto (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The objectives of this study were to find out whether or not there was a significant improvement before and after the treatment on the eleventh grade students’ reading comprehension scores at one Islamic senior high school in Palembang by using Subtext strategy and to find out whether or not there was a significant difference on the eleventh grade students’ reading comprehension scores between the students who were taught by using Subtext Strategy and those who were not. In this study, Quasi Experimental Design using pretest-posttest nonequivalent groups design was used. There were 60 students taken as sample. Each class consisted of 30 students from class XI IPS 2 as control group and class XI IPS 3 as experimental group. In collecting the data, reading comprehension test was used. The test was given twice to both experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The findings showed that the p-output from paired sample t-test (sig2-tailed) was 0.000 which was lower than 0.05 and t-value 11.399 was higher than t-table with df=29 (2.0452). The result of p-output from independent sample t-test was 0.001 which was lower than 0.05, and the t-value 3.465 was higher than t-table with df=58 (2.0017). It means that teaching reading narrative text by using Subtext strategy had significant effect on the students’ reading comprehension scores.